The tragedy of the unreliable narrator in The Girl Chewing Gum. Issue 2 (18th February 2012) - Proctor, Jennifer
As a short experimental work about the constructedness of the cinematic image, the film expresses anxieties about our inability not only to control filmic representation, but to impose order in our everyday lives. The film further reveals a pressing desire to turn our lives into movies – and a sadness that results from that impossibility.